Relationship Between Dietary Patterns and Chronic Diseases in Rural Population: Management Plays an Important Role in the Link - Li, Tiantian; Guan, Lizheng; Wang, Xuan; Li, Xiaoying; Zhou, Cui; Wang, Xianyun; Liang, Wannian; Xiao, Rong; Xi, Yuandi (Frontiers in Nutrition, 2022)
Objective Health dietary pattern is related with reduced risk of chronic metabolic disease, but the benefits were not fully clear in Chinese population. The aim of this study is to explore the association between dietary patterns and multiple chronic metabolic diseases in middle-aged and elderly Chinese. Methods A total of 718 Chinese adults aged ≥ 45 who lived in Huairou regions of Beijing were included in the present cross-sectional analysis from 2019 to 2020. Dietary data was obtained by food frequency questionnaires. Dietary patterns were identified by principal components analysis. Logistic regression analysis and hierarchical analysis were used to examine the relationship among dietary patterns, health management and noncommunicable diseases. Results Five dietary patterns were discovered in the subjects. The pattern with the higher percentage of energy supply by lipid was a risk factor for hypertension (OR=2.067, p=0.013). Lower energy intake (OR=0.512, p=0.012) and reasonable ratio of dietary energy supply (OR=0.506, p=0.011) were beneficial to diabetes. The substitution of potato for grain might be an effective way reducing diabetes as well (OR=0.372, p＜0.001). The higher intake of high-quality protein was the protect factor for coronary heart disease (OR=0.438, p=0.008). Moderate intervention (OR=0.185, p=0.033) and appropriate health education (OR=0.432, p=0.016) could greatly subserve the prevention of chronic diseases, especially for hyperlipidemia. Male was more likely to be affected by health education, intervention and follow-up than female. The prevalence of multimorbidity was higher in female (43.2%) than male (41.5%). The staple food intake and health management were also the important factors to prevent multimorbidity. Conclusion Dietary pattern with appropriate energy intake, reasonable source of energy supply, high quality of macronutrients and moderate management was associated with decreased risk of chronic metabolic diseases. Further studies are needed to clarify the cause–effect relationship between dietary patterns, health management and chronic diseases, and give suggestions to chronic metabolic diseases prevention in middle-aged and elderly people in rural area.